PENINGKATAN MINAT BELAJAR DAN HASIL BELAJAR KARYA INOVATIF MELALUI PENERAPAN STRATEGI KONSTRUKTIVISME - Lubis, Desy Afyanty (Universitas Negeri Medan, 2013)
ABSTRACT This research aims to find out : 1) the learning achievement of innovative work of college students taught by constructivism teaching strategy; 2) the increasing of learning achievement of innovative works; and 3) lecturer activities in the implementation of constructivism teaching strategy. This research was conducted at FT Unimed in study program of Make-Up on even semester in academic year of 2011/2012. The subject of this research is college students of Make up Education of FT Unimed that consist of 23 persons. In this research the data was collected through (1) observation sheet; (2) questionnaire; (3) observation and (4) field recording. This research is a classroom action research with 2 cycles in which each cycle consist of two sessions. Each cycle consist of planning, action, observation and reflection steps. The results of research indicates that : 1) the learning achievement of innovative work of college student on cycle 1 has an average = 65,00; 2) the learning achievement of college student in cycle 2 has an everage = 80,87; 3) there is increasing of learning activity of colege student and lecturer activity through the implementation of constructivism teaching strategy; 4) the increasing of learning interest of college student of 15 perssons ( 65,22%) is in good category in cycle 1 to be 21 persons (95.65%), and 13 persons (56.52%) in high category and 9 persons (39.13%) in good category. Therefore it indicates that Contructivism Teaching Strategy can increase the learning interest and learning achievement of innovative work. Kata Kunci : Minat belajar, hasil belajar, strategi konstruktivisme.